Pengaruh Pelayanan SDM Terhadap Tingkat Kepuasan Pasien di Pelayanan Rawat Jalan RS X Jambi (Analisis Perbandingan Pasien Umum dan BPJS) - Ririn Noviyanti Putri (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Health services require hospitals to provide quality services in accordance with the needs and desires of patients with reference to the code of ethics profession. Hospital demand in providing good service quality can improve the degree of patient satisfaction. Patient satisfaction is a common problem that often occurs in the hospital. This study aims to determine the effect of human resources service on patient satisfaction and see the ratio of the level of satisfaction between general patients and BPJS. This research is a comparative and with cross sectional approach. The sample in this study were general patients and BPJS who treated in outpatient installation as 108 respondents using chi-square statistical test and T test. The results showed that there were eight variables related to patient satisfaction level, namely educational level (p=0,0001), job status (p=0.0001), membership status (p=0,001), Service of human resources (p=0.0001), Service procedures (p=0.0001), Service of pharmacy (p=0.0001), Comfort (p=0,012), And patient relationship with hospital staff (p=0,0001) and there was difference of satisfaction level between general patient and BPJS (p=0.0001). Human resources services affect the level of patient satisfaction and there is difference of satisfaction level between general patient and BPJS. Suggestions for hospitals to continuously evaluate services by implementing the Plan Do Check Act (PDCA) cycle, so that the shortcomings that occur during the service process can continue to be minimized.